2016
DOI: 10.1038/srep20263
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in global microRNAome and transcriptome reveal complex miRNA-mRNA regulated host response to Japanese Encephalitis Virus in microglial cells

Abstract: Microglia cells in the brain play essential role during Japanese Encephalitis Virus (JEV) infection and may lead to change in microRNA (miRNA) and mRNA profile. These changes may together control disease outcome. Using Affymetrix microarray platform, we profiled cellular miRNA and mRNA expression at multiple time points during viral infection in human microglial (CHME3) cells. In silico analysis of microarray data revealed a phased pattern of miRNAs expression, associated with JEV replication and provided uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 50 publications
2
51
1
Order By: Relevance
“…We previously reported NOTCH‐mediated modulation of inflammation in JEV‐infected microglial cells (Kumari et al . ). Several reports suggested that the NOTCH signaling pathway may cross‐talk with TLR signaling pathway to control inflammation (Hu et al .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…We previously reported NOTCH‐mediated modulation of inflammation in JEV‐infected microglial cells (Kumari et al . ). Several reports suggested that the NOTCH signaling pathway may cross‐talk with TLR signaling pathway to control inflammation (Hu et al .…”
Section: Resultsmentioning
confidence: 97%
“…NOTCH pathway involves inflammatory cytokine production upon JEV infection (Kumari et al . ). Let‐7a/b expression can induce TNFα in microglia (Lehmann et al .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In addition, several of the differentially expressed microRNAs were found common to the previous published reports for example, miR‐21, miR‐101‐3p, miR‐32‐5p, miR‐4695‐3p, miR‐432‐5p, miR‐205, miR‐450b‐3p, miR‐3613‐5p, miR‐190a, miR‐299‐5p, miR‐4286,miR‐1264, miR‐193a‐3p, miR‐138, miR‐3182, miR‐19a, miR‐1260b, miR‐3074, miR‐374b, miR‐588, miR‐597, miR‐487b, miR‐676, miR‐196a, miR‐539‐3p, miR‐802, miR‐629‐3p,miR‐301a‐3p, miR‐3156, miR‐222‐5p, and miR‐29b‐3p. Consequently, the previous and current study indicates that these microRNAs might be relevant to JEV infection in human microglial cells . Moreover, there are two pairs of microRNA and gene targets, which were consistent with the previous report .…”
Section: Discussionmentioning
confidence: 99%